Pengaruh Model TANDUR terhadap Kemampuan Berpikir Kritis Siswa Pada Pembelajaran IPS - Agustina, Erry; Kurnia, Dadang; Gusrayani, Diah (Jurnal Pena Ilmiah, 2019)
Social Sciences is directed at mastering competencies not only in their knowledge but in a creative, creative and independent culture of scientific thinking, TANDUR models are needed to help students who have difficulty in learning subject matter. The purpose of this study was to study the effect of the TANDUR model on students' critical thinking skills in social studies learning. This study used the experimental method with the design of the pretest-posttest control group. The study population was all fifth grade students of North Sumedang Elementary School with a sample of fifth grade students at Ketib elementary school as an experimental class and Padasuka IV elementary school as a control class. The conclusions of the research are: 1) Social studies learning using the TANDUR model can improve students 'thinking skills, 2) Social studies learning using the TANDUR model is significantly better in improving students' thinking skills using conventional learning.